STUDENT PERCEPTION OF INTERACTIONS BETWEEN STUDENTS AND LECTUTERS, LEARNING MOTIVATION, AND ENVIRONMENT DURING PANDEMIC COVID-19 - Amin, Alfauzan; Alimni; Lestari, Meri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2021)
Online learning is one form of network utilization that can develop the way of students in the education process. The descriptive analysis of this study examined students' perceptions of online learning models related to interactions between students and lecturers, learning motivation, and student learning environments to support them produce better result from online teaching and learning activities. The sample in this study are 128 students in one of the universities in Bengkulu who have been involved in online learning during the Coronavirus disease 2019 pandemic. Based on questionnaires that have been investigated, the researchers found that students had problems interacting with other students as well as lectures. This is demonstrated by a upper percentage of 65.62% students' disapproval of statements stating that student interaction in online classes already supports them in the learning process. Meanwhile, 52.34% of students have very high learning motivation even in quarantine due to covid-19. As well as the learning environment, 70.31% of students felt that the learning environment is less supportive of them in the learning process of teaching in online learning. Therefore, in support students to increase their interactions and learning environments, lecturers can create groups on social media to communicate and improve the atmosphere of the learning environment between students and the others.